Agrobacterium-mediated Genetic Transformation of Mungbean (Vigna radiata (L.) Wilczek) - Islam, Mohammad Nurul; Islam, Kazi Tariqul (Plant Tissue Culture and Biotechnology, 2011)
Kew words: Mungbean, Vigna radiata, BINA mug-5,Transformation, nptII, GUS D.O.I. 10.3329/ptcb.v20i2.6918 Plant Tissue Cult. & Biotech. 20(2): 233-236, 2010 (December) - Short communication